Gastric variceal hemorrhage treated with percutaneous transhepatic embolization with balloon-occluded antegrade transvenous obliteration - Prasoon P. Mohan; Jesus Beltran-Perez; Preeti P. Ahlman (Society of Gastrointestinal Intervention, 2019)
We report a case of gastric variceal hemorrhage where high model for end-stage liver disease score and the complex gastric variceal anatomy precluded the use of both transjugular intrahepatic porto-systemic shunt and standard balloon-occluded retrograde transvenous occlusion (BRTO) procedures respectively. The patient was successfully managed by percutaneous transhepatic coil embolization combined with BRTO. It is of great importance to obtain an accurate cross-sectional image to evaluate the anatomical variances of gastric varices that will lead to appropriate vascular access and to chose a suitable embolization method.